Nutidens Samhandelsformer og deres landbrugsmæssige Virkninger. Foredrag, sept. 1939. - Skovgaard, K. (Tidsskrift for Landøkonomi, 2018)
Nutidens Samhandelsformer og deres landbrugsmæssige Virkninger. Foredrag, sept. 1939.